2011
DOI: 10.1590/s1808-86942011000300017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dexamethasone on post-tonsillectomy nausea, vomiting and bleeding

Abstract: It has been stated, that the administration of Dexamethasone has an impact on the morbidity following tonsillectomy.Objective: To re-calculate the blood values for Dexamethasone when given as fixed doses and to evaluate the effect of Dexamethasone on post-operative nausea, vomiting and bleeding rates following tonsillectomy. Materials and methods:The charts of 272 children (2-15 years) who had undergone tonsillectomy were analyzed. The rates of post-operative nausea, vomiting and bleeding in relation to Dexame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…This may be caused by the more frequent occurrence of PTAs in men, and the subsequently increased rate of uvula edema. However, upto-date studies and meta-analyses have failed to show an increased risk of PTH after dexamethasone application [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…This may be caused by the more frequent occurrence of PTAs in men, and the subsequently increased rate of uvula edema. However, upto-date studies and meta-analyses have failed to show an increased risk of PTH after dexamethasone application [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…In the 3 years since the release of the study by Czarnetzki et al [23], there have been several studies published which demonstrate no increased risk of bleeding with dexamethasone [28,62,63]. Furthermore, some of the trials actually found a significantly reduced risk of bleeding with dexamethasone versus placebo.…”
Section: Further Inquiry: 2009-2012mentioning
confidence: 99%
“…They were all retrospective case note reviews and two of them retrieved 2 week follow-up data. In one of the studies, a single method of tonsil dissection was used, 61 while in the other studies, there were several methods recorded. 54 58 In the retrospective chart review conducted by Conley and Ellison, 54 children who received dexamethasone were operated on using a standard surgical technique-cold-knife dissection and snare and haemostasis was achieved using tonsillar packs dipped in bismuth subgallate-phenylephrine hydrochloride mixture followed by suction electrocautery and a 3 min observation period.…”
Section: Included Studiesmentioning
confidence: 99%
“…The report of one study specifies that dexamethasone was administered or withheld according to the anaesthetist's preference. 61 NSAIDs were administered Table 2 Risk of bias for randomized studies which compare dexamethasone with another intervention and reported haemorrhage rate. Dex, dexamethasone; ED, emergency department; NSAID, non-steroidal anti-inflammatory drug; POD, postoperative day; PONV, postoperative nausea and vomiting; postop, postoperative…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation